Implementasi Manajemen Kurikulum 2013 pada Anak Berkebutuhan Khusus (ABK) untuk Tunagrahita di Sekolah Luar Biasa Negeri 033 Tembilahan - Gusmuri Nengsih (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2021)
The 2013 Curriculum is a set of plans and arrangements regarding the objectives, content, and learning materials used as the latest guidelines for the implementation of education in Indonesia which began in 2013. The 2013 curriculum is implemented in all subjects in all schools that apply the curriculum both public and outside schools normal The application of the 2013 curriculum in special schools is proof of the absence of discrimination for children with special needs in obtaining their educational rights.The results of the study implementation of the 2013 curriculum management for children with special needs for mental retardation in State Special School (SLBN) 033 Tembilahan was not all in accordance with the standards in the 2013 curriculum. This can be seen from the organization and implementation process of learning that simplifies learning material in accordance with the character of mentally retarded children.